2019
DOI: 10.1111/are.14251
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary supplementation of Astragalus membranaceus , Codonopsis pilosula , and Glycyrrhiza uralensis extract mixture on growth performance, haematological parameters and hepatopancreatic performance in juvenile Pacific white shrimp ( Litopenaeus vannamei )

Abstract: Pacific white shrimp is the major farmed shrimp species in the world. It is known to be very sensitive to the environmental and management changes such as intensification, which is one of the primary necessities to increase shrimp production, but represents a stressful condition, and needs to be managed properly to diminish its negative effects in aquaculture. In this study, juvenile Pacific white shrimp were fed diets supplementing with equal quantities of Astragalus membranaceus, Codonopsis pilosula and Glyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 78 publications
0
4
0
Order By: Relevance
“…The application of dietary herbal extracts in aquaculture has been described in various studies. Thus, findings proved that herbal extract is effective in the immune response and disease resistance of different species of cultured shrimp (Syahidah et al, 2015;Prathomya et al, 2019;Santhosh et al, 2023). The present study was designed to determine the effective Jan 5, 2024 https://afri.et/helix/article/view/128 herbal extracts incorporated in the diets on the health of whiteleg shrimp (L. vannamei) with specificity on the use of P. urinaria and C. quadrangulare against V.parahaemolyticus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The application of dietary herbal extracts in aquaculture has been described in various studies. Thus, findings proved that herbal extract is effective in the immune response and disease resistance of different species of cultured shrimp (Syahidah et al, 2015;Prathomya et al, 2019;Santhosh et al, 2023). The present study was designed to determine the effective Jan 5, 2024 https://afri.et/helix/article/view/128 herbal extracts incorporated in the diets on the health of whiteleg shrimp (L. vannamei) with specificity on the use of P. urinaria and C. quadrangulare against V.parahaemolyticus.…”
Section: Discussionmentioning
confidence: 99%
“…The percentage increase in a particular compartment can be due to the recruitment of cells from non-circulating compartments of the hemolymph, induced cellular proliferation, or rapid differentiation in response to antigenic challenge (Aladaileh et al, 2008). Astragalus membranaceus, Codonopsis pilosula, and Glycyrrhiza uralensis supplementation improved the THC and granulocyte count in L. vannamei (Prathomya et al, 2019). Supplementing shrimp with herbal extracts of Boerhaavia diffusa as well produced similar results of improving THC and granulocytes (Chithambaran and David,2014), P.amarus (Ngo et al, 2020), P.urinaria and T.cattapa enhanced innate immunity and THC in P.vannamei as reported by Isnani et al(2021).…”
Section: Discussionmentioning
confidence: 99%
“…In the last decades, there has been growing research interest in using plant extracts as fish immunostimulants. [151][152][153] Immunostimulants are naturally occurring or synthetic compounds aimed at stimulating the immune system through specific (vaccine or antigen) and nonspecific actions (without antigen specificity). [154][155][156] Various research demonstrated that intraperitoneal injection or oral administration of plant extracts enhanced phagocytic and lysosomal function, respiratory burst and complement activity, and serum protein level in some distinct fish species.…”
Section: Referencesmentioning
confidence: 99%
“…Apart from the effects of anti‐stress, herbal medicines were well studied to improve the immunity of aquatic animals. In the last decades, there has been growing research interest in using plant extracts as fish immunostimulants 151–153 . Immunostimulants are naturally occurring or synthetic compounds aimed at stimulating the immune system through specific (vaccine or antigen) and non‐specific actions (without antigen specificity) 154–156 .…”
Section: Use Of Medicinal Plants As Anti‐stress and Immunostimulantsmentioning
confidence: 99%
“…Several studies have focused on using plant extracts as fish immunostimulants ( Prathomya et al. 2019 ; Rafieepour et al.…”
Section: Introductionmentioning
confidence: 99%